INFORMATION TECHNOLOGY INTEGRATION FOR ACADEMIC ADMINISTRATION OPTIMIZATION - I Made Sudana; Soedjono; Kamsidjo Budi Utomo; Ghufron Abdullah (Universitas PGRI Semarang, 2025)
The purpose of this research is to find an ICT integration system in academic administration, provide input in the form of recommendations to the Institute, especially the academic information system management unit that has been strengthened from the previous system. The research method used is quantitative descriptive research using questionnaires as the data collection technique. the sample in this study consisted of lecturers, students and managers of Academic Information Systems from three former IKIP Private Universities in Central Java, namely UPGRIS, Univet and Unwihda. Data analysis techniques used using descriptive analysis using percentage. In general, the integration of ICT in academic administration, UPGRIS 93.79% with a very good category and UNIVET 86.17% with a very good category while UNWIDHA still needs to be improved because it is still relatively simple. (60%), while UNWIDHA still needs to be improved because it is still relatively simple. Academic SIM sections that are often visited by users include; (a) lecture information, (b) lecture and exam schedules, (c) semester exam evaluation results, (d) scientific paper guidelines, (d) Lecturer Information. Most respondents stated that information related to academic issues was categorized as complete.